Justice Sector Corruption: Will Indonesia Neutralize it? - Idy, Muhammad Yunus; Sahabuddin, Andi Arfan (International Journal of Criminology and Sociology, 2021)
Background: Though there are vigorous efforts made to fight corruption attitude and behavior, in Indonesia the judiciary sector is still characterized by the existence of rampant widespread corruption acts of crime. For instance, there are many judges who have been caught being bribed across the country. From the available data, of the 19 judges at the Corruption Eradication Commission, 53% are those who make up the Corruption Adhoc judges, while the remaining 47% are career judges. Objective: This research was conducted to determine the corrupt behavior of judges in relation to carrying out their duties and authority in upholding justice. Method: The study applied a normative juridical research method, which established that corruption behavior exhibited by judges in handling cases is still prone to criminal acts of corruption, is detrimental to justice seekers. Conclusion: Thus, the judge's corrupt behavior as the foremost law enforcer can be prevented as early as possible, if justice is to be upheld at a national level.